Effect of water containing organic acids on aspiration pneumonia-causative bacteria in the biofilm on the tooth surface - Tomoko Umezawa; Masahiro Ryu; Akinori Tasaka; Takayuki Ueda; Kazuyuki Ishihara; Kaoru Sakurai (Elsevier, 2017)
Background/purpose: The tooth surface is a source of oral microbes in dentulous individuals, it is difficult for elderly people requiring nursing care to perform mechanical tooth cleaning by themselves. The objective of this study was to investigate the antimicrobial effect of water containing organic acids (WOA) made by some organic acids as food additives on chemical cleaning for elderly people on aspiration pneumonia-causative bacteria in the biofilm on the tooth surface. Materials and methods: Ninety-six specimens made from bovine incisors were divided into four groups and incubated with one of four aspiration pneumonia-causative bacteria. Each group was further divided into six subgroups according to treatment as follows: control group (DW), chlorhexidine gluconate solution group (CHX), WOA group (WOA), ultrasonic treatment in distilled water group (DW-U), ultrasonic treatment in chlorhexidine gluconate solution group (CHX-U) or ultrasonic treatment in WOA group (WOA-U). After treatment, the levels of viable microbes in the biofilm were evaluated by quantitative adenosine triphosphate analysis and compared among the six groups. Results: For every evaluated microbe, there were significant differences between DW and WOA, and DW and WOA-U. However, there was no significant difference among the WOA, DW-U, CHX-U and WOA-U groups. These results suggested that the antimicrobial effect of WOA on microbes attached to the tooth surface was similar to that of ultrasonic cleaning. Conclusion: WOA has an antimicrobial effect on microbes in the biofilm on the tooth surface. Keywords: mouthwash, dental enamel, microbiology, dental care for aged, antibacterial agent